A Word from old Uyghur to the present: Alig - SAĞOL YÜKSEKKAYA, GÜLDEN (My University, 2022)
In this study, we examine the etymology of the the word alig, which has appeared in various Turkic lan-guages starting with Old Uyghur. Researchers have so far put forth different theories regarding the origins of this word, which survives today in different parts of the Turkic-speaking world with various phonetic and semantic changes. Some have associated it with al-\"to take\" (\"almak\") (< al-i-g), which is semantically problematic, or with hypothetical roots which they reconstruct variously as *al (< al+ig), *al-or *ali-. Con-sidering earlier proposals, we narrow down the set of possible etymologies for alig in accordance with their relative merits.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Sosyoloji; Social Sciences and Humanities; History; Sociology; TARİHÇE; Sanat ve Beşeri Bilimler; Sanat ve Beşeri Bilimler (AHCI); ASYA ÇALIŞMALARI; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); HISTORY; ARTS & HUMANITIES; Arts & Humanities (AHCI); ASIAN STUDIES; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Genel Sosyal Bilimler; Koruma; Sanat ve Beşeri Bilimler (çeşitli); Genel Sanat ve Beşeri Bilimler; Sosyal Bilimler ve Beşeri Bilimler; General Social Sciences; Conservation; Arts and Humanities (miscellaneous); General Arts and Humanities; Social Sciences & Humanities; Old Uyghur; Old Turkic; al?g; etymology